DIMETILSULFOKSID SEBAGAI ENHANCER TRANSPOR TRANSDERMAL TEOFILIN SEDIAAN GEL - Resty Annisa Damayanti; Tedjo Yuwono (Universitas Ahmad Dahlan, 2013)
Dimethylsulfoxide (DMSO) has been intensively studied the 19th century. This substance is used as a medicine and solve. It can also be used as an absorption enhancer of various drugs, either synthetical or herbal medicines. This study conducted with DMSO as transdermal absorption enhancer of theophylline, which often used as an anti-cellulite dosage forms. The experiments studied in vitro transdermal absorption of theophylline in gel dosage forms, containing 7% theophylline dan various concentration of DMSO i.e. 0% , 3%, 5% and 7% DMSO respectively. These studies used skin membrane of Wistar strain male rats in a vertical type diffusion Cell. The results indicated that DMSO was very potential as a permeation enhancer theophylline, the formula containing 7% DMSO increased the theophylline transport from 17,9 µg to 139,1 µg.